2021
DOI: 10.24191/ajue.v17i2.13398
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction as a Mediator between Leadership Styles and Organisational Commitment of Teachers in Malaysia

Abstract: To better understand the organisational commitment of teachers, the current study examined job satisfaction as a mediator between organisational commitment and the three dimensions of leadership, namely transformational, transactional and passive-avoidant. The study involved 381 school teachers in Malaysia, and the multiple-model analysis used showed partial mediation on the negative association of passive-avoidant leadership style with teachers’ commitment to their organisation. The study found a relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
1
14
1
Order By: Relevance
“…Nonetheless, given that the direct link between commitment and leadership behaviours was positive and insignificant, it can be inferred that job satisfaction partially mediated the link between organisational commitment and leadership behaviours. This contrasted with research by Hendri (2018), Silitonga et al (2020), andHalim et al (2021) that showed job satisfaction mediated the association between commitment and leadership behaviours. However, research by Banjarnahor et al (2018) supported the results by indicating that job satisfaction partially mediated the link between the two variables.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Nonetheless, given that the direct link between commitment and leadership behaviours was positive and insignificant, it can be inferred that job satisfaction partially mediated the link between organisational commitment and leadership behaviours. This contrasted with research by Hendri (2018), Silitonga et al (2020), andHalim et al (2021) that showed job satisfaction mediated the association between commitment and leadership behaviours. However, research by Banjarnahor et al (2018) supported the results by indicating that job satisfaction partially mediated the link between the two variables.…”
Section: Discussioncontrasting
confidence: 95%
“…Job satisfaction has been identified as a mediator of organisational commitment because employees become more committed to their work if they feel satisfied (Halim et al, 2021). Studies ( Banjarnahor et al, 2018;Halim et al, 2021;Ishak & Romle, 2015;Mwesigwa et al, 2020;Nadia & Azzman, 2020;Nanjundeswaraswamy, 2023;Sušanj & Jakopec, 2012;Yousef, 2000) have examined the mediating effect of job satisfaction on the influence of leadership behaviours and organisational commitment of academic staff. However, conceptual and population gaps emerged.…”
Section: Job Satisfaction Leadership Behaviours and Organisational Co...mentioning
confidence: 99%
“…The adversity quotient is an essential component of organizational commitment to achieving a career (Kurniawan et al, 2020). Organizational culture will always exist in organizations, especially in organizational commitment (Kumar, 2016), and job satisfaction has a positive effect on teachers' commitment (Halim et al, 2021;Kedir et al, 2021). This research finding can be a beneficial guideline for the Ministry of Education and Culture, district leadership, school leaders, high school principals, school supervisors, teachers, and practitioners.…”
Section: Findings and Discussionmentioning
confidence: 66%
“…Analysis used double linear regression. Job satisfaction had a positive effect on teachers' commitment (Halim et al, 2021;Kedir et al, 2021).…”
Section: Findings and Discussionmentioning
confidence: 95%
“…The findings indicated that the three components of organizational commitment are influenced by both transformational and transactional leadership variables, although the size and direction of their effect varies. Despite the similarities between transactional and transformational leadership, prior research has indicated that transformational leaders' actions have a higher favorable influence on teachers' outcomes, including their job satisfaction, organizational commitment, and organizational citizenship behavior [3], [4].…”
Section: Discussionmentioning
confidence: 99%